Static and Dynamic Properties of Portal Frames Composed of Built-Up Sawn Square Timber - Kohei Komatsu; Akihisa Kitamori (Masyarakat Peneliti Kayu Indonesia, 2012)
In order to propose an alternative structural element to be used for wooden dwelling houses in rich forest area, we paid attentions to a portal frame structure which is composed of not glulam but built-up members whose raw materials are dried sawn timbers taken from plantation grown forest. For establishing design procedure of the structural element, we made two different types of portal frames and conducted, at first, basic dynamic test to estimate natural frequency and dumping factors by fixing small shake excitation machine on the portal frames, then static push-pull cyclic loading tests were conducted until failure. The natural frequency of both portal frames was almost same but the higher order frequencies were likely to be affected by the difference of shear reinforcement of built-up members by hardwood dowels. While on static properties, as both portal frames failed in brittle manner due to bending failure at column or tear off at connection plate made of compression wood, further improvement of connection system was required for obtaining more stable alternative elements to glulam.